RETRACTED: Dihydroartemisinin Suppresses the Tumorigenesis and Cycle Progression of Colorectal Cancer by Targeting CDK1/CCNB1/PLK1 Signaling - Yi, You-Cai; Liang, Rui; Chen, Xiao-Yu; Fan, Hui-Ning; Chen, Ming; Zhang, Jing; Zhu, Jin-Shui (Frontiers in Oncology, 2021)
Dihydroartemisinin (DHA), a well-known antimalarial drug, has been widely investigated as its anti-tumor effects in multiple malignancies. However, its effects and regulatory mechanisms in colorectal cancer (CRC) are still unproved. In this study, the in vitro experiments including CCK8, EdU, Transwell, flow cytometry analyses and in vivo tumorigenesis model were conducted to assess the effects of DHA on the bio-behaviors of CRC cells. Additionally, RNA-seq combined with gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses was used to obtain the targets of DHA and these were verified by molecular docking, qRT-PCR and Western blot. As a result, we found that DHA significantly suppressed the proliferation, DNA synthesis and invasive capabilities, and induced cell apoptosis and cell cycle arrest in HCT116, DLD1 and RKO cells in vitro and in vivo. Further analyses indicated that the targets of DHA were predominantly enriched in cell cycle-associated pathways, including CDK1, CCNB1 and PLK1, and DHA could bind with CDK1/CCNB1 complex and inhibit the activation of CDK1/CCNB1/PLK1 signaling. Moreover, cucurbitacin E, a specific inhibitor of CDK1/CCNB1 axis enhanced the inhibitory effects of DHA on DNA synthesis and colony formation in HCT116 and DLD1 cells. In short, DHA could suppress the tumorigenesis and cycle progression of CRC cells by targeting CDK1/CCNB1/PLK1 signaling.